A multi-hazard approach to disaster-resilient and sustainable infrastructure development - Clairine Fedhora; Oktaviani Novitasari; Visky Alfani; Eka Fauzia Ramadhani; Alidyatul Masruroh (Calamity: A Journal of Disaster Technology and Engineering, 2026)
Background: Indonesia is highly vulnerable to natural disasters, making the development of disaster-resilient and sustainable infrastructure a strategic necessity for disaster risk reduction and long-term development. This study aims to examine the concepts, principles, and challenges of developing resilient and sustainable disaster infrastructure based on recent literature. Methods: The research employs a qualitative descriptive approach through a literature review of scientific journal articles, policy reports, and publications from national and international institutions. Finding: The findings indicate that infrastructure resilience is not solely determined by physical strength but also by the integration of disaster risk analysis, sustainability-oriented planning, and adaptive governance and innovation. Multi-hazard risk-based approaches and the use of digital technologies play a significant role in enhancing the effectiveness of disaster infrastructure development. However, major challenges remain in terms of institutional capacity and coordination among stakeholders. Conclusion: This study concludes that the development of resilient and sustainable disaster infrastructure requires an integrated approach that combines technical, policy, social, and environmental aspects to support inclusive and sustainable development. Novelty/Originality of this article: This article contributes originality by synthesizing recent literature to frame disaster-resilient and sustainable infrastructure as an integrated multi-hazard system that combines engineering resilience, digital technologies, and adaptive governance, offering a comprehensive perspective aligned with contemporary disaster technology and engineering challenges.